Quantification of 5-Methylcytosine and 5-Hydroxymethylcytosine in Genomic DNA from Hepatocellular Carcinoma Tissues by Capillary Hydrophilic-Interaction Liquid Chromatography/Quadrupole TOF Mass Spectrometry - Chen, Ming-Luan (2013)
BACKGROUND: 5-Methylcytosine (5-mC) is an important epigenetic modification involved in development and is frequently altered in cancer. 5-mC can be enzymatically converted to 5-hydroxymethylcytosine (5-hmC). 5-hmC modifications are known to be prevalent in DNA of embryonic stem cells and neurons, but the distribution of 5-hmC in human liver tumor and matched control tissues has not been rigorously explored. METHODS: We developed an online trapping/capillary hydrophilic-interaction liquid chromatography (cHILIC)/in-source fragmentation/tandem mass spectrometry system for quantifying 5-mC and 5-hmC in genomic DNA from hepatocellular carcinoma (HCC) tumor tissues and relevant tumor adjacent tissues. A polymer-based hydrophilic monolithic column was prepared and used for the separation of 12 nucleosides by cHILIC coupled with an online trapping system. Limits of detection and quantification, recovery, and imprecision of the method were determined. RESULTS: Limits of detection for 5-mC and 5-hmC were 0.06 and 0.19 fmol, respectively. The imprecision and recovery of the method were determined, with the relative SDs and relative errors being <14.9% and 15.8%, respectively. HCC tumor tissues had a 4- to 5-fold lower 5-hmC content compared to tumor-adjacent tissues. In addition, 5-hmC content highly correlated with tumor stage (tumor-nodes-metastasis, P = 0.0002; Barcelona Clinic liver cancer, P = 0.0003). CONCLUSIONS: The marked depletion of 5-hmC may have profound effects on epigenetic regulation in HCC and could be a potential biomarker for the early detection and prognosis of HCC.